THE EFFECTS OF VOCABULARY AND GRAMMAR MASTERY ON STUDENT'S ABILITY TO WRITE ENGLISH (Survey at Private Vocational School in East Jakarta) - Kamaludin Kamaludin; Supadi Supadi (INFERENCE: Journal of English Language Teaching, 2020)
This study aimed to determine the effect of mastery of vocabulary on students' ability to write English. Furthermore, to determine the effects of vocabulary and grammar mastery on students' ability to write English. The research method used was a survey method; samples were taken as many as 70 students with a simple random technique. Data collection using the instrument: tests, data analysis using descriptive statistics such as finding the mean, median, mode, standard deviation, multiple linear regression, normality test data, hypothesis testing, and inferencial statistics to find the correlation coefficient with the calculated T-test and F calculated. The research process takes a month, where the researcher gives the direct tests in class XI of vocational school. The research is done from September to January 2020. The hypothesis of this study is 1) There is a significant influence of mastering vocabulary and mastering grammar together on student's ability to write English, 2) There is a significant influence of mastering vocabulary on student's ability to write English, 3) There is a significant influence of mastering grammar on student's ability to write English. The research method used statistics with the help of Microsoft Excel and SPSS 22.0. Conclusions from the results of this study's analysis: There is a significant influence of mastering vocabulary and grammar mastery on students' ability to write English at private Vocational School in east Jakarta. This is evidenced by the acquisition of Sig = 0,000 < 0.05 and F count = 9,403. Second, there is a significant influence of vocabulary mastery on students' writing English at a private Vocational School in east Jakarta. This is evidenced by the acquisition of Sig = 0,029 < 0,05 and t count = 2,229. Third, there is a significant influence of grammar mastery on student's ability to write English at a private Vocational School in east Jakarta. This is evidenced by the acquisition of Sig = 0,002 < 0,05 and t count = 3,304.